Implantable CMOS image sensor with incident‐angle‐selective pixels. Issue 13 (1st June 2019) - Sugie, K.; Sasagawa, K.; Guinto, M.C.; Haruta, M.; Tokuda, T.; Ohta, J.
Abstract : Angle‐selective pixels fabricated by using metal layers of the image sensor chip are proposed. Four incident‐angle‐selective pixels share one aperture. The selective pixel has a peak at 40° and full width at half maximum of ∼23°. An image sensor composed of normal and angle‐sensitive pixels was designed and fabricated. The reconstruction of a high‐resolution image from the blurred image using five different views is demonstrated.